Investigating the effect photodegradation has on natural fibres at a microscopic level. Issue 5 (September 2019) - DeBattista, Roslyn; Tidy, Helen; Clark, Matthew
Abstract: It is a known fact that when fabric is left exposed to sunlight photodegradation occurs. However, no study has ever looked at the photodegradation that occurs to individual fibre filaments as commonly recovered from a scene of crime. To look at photodegradation of individual fibres, wool and cotton fabric were dyed using CI Acid Red 27 and CI Direct Red 80 respectively at two depths of shade, 0.25% and 2.0% owf. Pieces of fabric and individual fibre samples were then placed in a Light Fastness Q-Sun 1000 Xenon test chamber which simulated exposure to sunlight over two time periods, 64 h (equivalent to one weeks sun exposure) and 128 hrs (equivalent to two weeks sun exposure). The resulting pieces of fabric and fibres where then examined using high power comparison microscopy, as well as graded for colour fading using SDC Grey Scale for Assessing Change in Colour (including half steps). Results show that in both fibre types, photodegradation occurs in all samples, however, the degree of fading is shown to vary within a given fibre population showing it is unpredictable in nature. Highlights: Application of a textile standard colour fading system in a forensic context. Photodegradation was found to occur on cotton and wool fabric samples. Fibres can fade unevenly along the same fibre length. Fibres dyed to a lower depth of shade tend to fade quicker. Shows a need for caution when interpreting fibres.